Perovskite solar cell and preparation method thereof
By introducing glycerol into the electron transport layer of perovskite solar cells, the performance of the electron transport layer is optimized, and the problem of low photoelectric performance and efficiency of existing perovskite solar cells is solved, and higher photoelectric performance and efficiency are achieved. Simplified the preparation process.
Patent Information
- Application Number
- CN202311009711.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The photoelectric performance and efficiency of existing perovskite solar cells still need to be improved, mainly due to the poor quality of the electron transport layer, the low electron mobility, and the film formation rate is greatly affected by factors such as ambient temperature.
Glycerol is introduced into the electron transport layer of perovskite solar cells to optimize the performance of the electron transport layer. The specific method includes forming a dense electron transport layer and a mesoporous electron transport layer on the transparent conductive layer, and adding glycerol to the dense electron transport layer to improve the viscosity and film formation quality of the material liquid.
By introducing glycerol, the performance of the electron transport layer is optimized, the photoelectric performance and efficiency of perovskite solar cells are improved, and the photoelectric conversion rate is high. At the same time, the preparation process is simplified and suitable for industrial applications.
Smart Images

Figure CN119486451A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar cells, and in particular to a perovskite solar cell and a preparation method thereof. Background Art
[0002] In recent years, perovskite solar cells have attracted extensive attention due to the advantages of perovskite materials such as long carrier diffusion length, adjustable band gap, high light absorption coefficient and low raw material cost. For example, halide perovskite solar cells are considered to be the third generation of solar cells, and the efficiency of single-junction lead-based perovskite solar cells is comparable to that of silicon-based solar cells. However, the optoelectronic performance and efficiency of existing perovskite solar cells still need to be improved. Summary of the invention
[0003] The present invention provides a perovskite solar cell and a preparation method thereof, which can improve the photoelectric performance and efficiency of the perovskite solar cell.
[0004] In one aspect of the present invention, a perovskite solar cell is provided, comprising a transparent conductive layer, an electron transport layer, a perovskite light absorbing layer and a hole transport layer stacked in sequence, wherein the electron transport layer comprises glycerol.
[0005] According to one embodiment of the present invention, the electron transport layer includes a dense electron transport layer and a mesoporous electron transport layer located between the dense electron transport layer and the perovskite light absorbing layer, and the glycerol exists in the dense electron transport layer.
[0006] According to one embodiment of the present invention, the electron transport layer is a titanium dioxide layer.
[0007] According to one embodiment of the present invention, the transparent conductive layer includes FTO conductive glass.
[0008] Another aspect of the present invention provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps: applying a first mixed solution containing an organic titanium source, a first solvent and glycerol on a transparent conductive layer to form a dense electron transport layer; applying a second mixed solution containing an inorganic titanium source and a second solvent on the dense electron transport layer to form a mesoporous electron transport layer; and sequentially forming a perovskite light absorption layer and a hole transport layer on the mesoporous electron transport layer to obtain the perovskite solar cell.
[0009] According to one embodiment of the present invention, before applying the first mixed liquid on the transparent conductive layer, the transparent conductive layer is pretreated, and the pretreatment process includes: cleaning the transparent conductive layer with a cleaning agent, drying it, and then performing ultraviolet ozone treatment; wherein the cleaning agent includes one or more of water, acetone, isopropyl alcohol, ethanol, and glass cleaning agent.
[0010] According to one embodiment of the present invention, the organic titanium source is calculated as titanium dioxide, and the molar ratio of the glycerol to the organic titanium source is 1:200 to 1:350.
[0011] According to one embodiment of the present invention, the organic titanium source includes diisopropoxy titanium bisacetylacetonate; and / or the first solvent includes n-butanol.
[0012] According to one embodiment of the present invention, the first mixed solution is spin-coated on the transparent conductive layer by a dynamic spin coating method, and then annealed at 110-130° C. for 8-12 min to form the dense electron transport layer.
[0013] According to one embodiment of the present invention, the inorganic titanium source includes titanium dioxide; and / or, the second solvent includes ethanol; and / or, the mass ratio of the inorganic titanium source to the second solvent is 1:(7-9); and / or, the second mixed liquid is spin-coated on the dense electron transport layer by static spin coating, and then annealed at 450-550°C for 40-70 minutes to form the mesoporous electron transport layer.
[0014] In the present invention, glycerol is introduced into the electron transport layer of the perovskite solar cell to optimize the performance of the electron transport layer, thereby improving the photoelectric performance and efficiency of the perovskite solar cell. At the same time, the perovskite solar cell of the present invention also has the advantages of simple preparation process and easy operation, which is conducive to practical industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A schematic diagram of the structure of a perovskite solar cell according to an embodiment of the present invention;
[0016] Figure 2 Steady-state photoluminescence spectra of the perovskite solar cells of Example 1 and Comparative Example 1 (the abscissa is wavelength (Wavelength), and the ordinate is photoluminescence intensity (PLintensity)));
[0017] Figure 3 The transient photoluminescence spectra of the perovskite solar cells of Example 1 and Comparative Example 1 (the abscissa is time (Times), and the ordinate is normalized photoluminescence intensity (Normalized PL intensity));
[0018] Figure 4 It is a curve diagram of the relationship between the current density and the voltage of the perovskite solar cells of Example 1 and Comparative Example 1 (the horizontal axis is voltage (Voltage), and the vertical axis is current density (Current Density)).
[0019] Explanation of the reference numerals: 1: transparent conductive layer; 11: first region; 12: second region; 2: electron transport layer; 21: dense electron transport layer; 22: mesoporous electron transport layer; 3: perovskite light absorbing layer; 4: hole transport layer; 5: counter electrode. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0021] In recent years, perovskite solar cells have attracted extensive attention due to their advantages such as long carrier diffusion length, adjustable band gap, high light absorption coefficient and low raw material cost. However, the photoelectric performance and efficiency of existing perovskite solar cells still need to be improved.
[0022] For example, the main functional layers of perovskite solar cells include electron transport layer, perovskite light absorption layer and hole transport layer, which is also called a "sandwich" structure. The electron transport layer can reduce the potential barrier between the electrode and the perovskite, promote the migration of carriers, and effectively block holes, thereby inhibiting the recombination of electrons and holes at the interface. It is crucial for efficient and stable perovskite solar cells. In the formal structure and the trans structure, the electron transport layer 2 material is usually titanium dioxide (TiO 2 ), tin dioxide (SnO 2 ), fullerene derivatives (PCBM), etc. Among them, TiO 2 It is a commonly used electron transport layer material in mesoporous nip-type perovskite solar cells.
[0023] However, due to the low electron mobility of the electron transport layer material and the film formation rate during the preparation of the electron transport layer being affected by ambient temperature and other conditions, the quality of the electron transport layer is poor and there are problems such as poor charge transfer capacity, especially for TiO 2 , it has problems such as large bandgap width and low electron mobility. In the process of preparing the electron transport layer by spin coating and other methods (especially in the process of preparing the dense electron transport layer by dynamic spin coating), the film formation rate of the electron transport layer is greatly affected by factors such as ambient temperature. For example, in an air atmosphere, a higher room temperature will increase the volatilization rate of the liquid used to form the electron transport layer in the preparation process of the dense electron transport layer, that is, increase the film formation rate, thereby affecting the film quality of the dense electron transport layer, which is not conducive to the photoelectric performance and efficiency of perovskite solar cells.
[0024] In view of this, an embodiment of the present invention provides a perovskite solar cell, such as Figure 1 As shown, the perovskite solar cell includes a transparent conductive layer 1, an electron transport layer 2, a perovskite light absorption layer (perovskite thin film layer) 3 and a hole transport layer 4 which are stacked in sequence, and the electron transport layer 2 includes glycerol.
[0025] In the embodiments of the present invention, based on the properties of the electron transport layer 2 in the perovskite solar cell, glycerol is introduced therein to optimize the performance of the electron transport layer 2, thereby improving the photoelectric performance and efficiency of the perovskite solar cell. For example, the perovskite solar cell can have both high open circuit voltage and photoelectric conversion efficiency and other properties.
[0026] According to the research and analysis of the inventors, by introducing glycerol into the electron transport layer 2, the charge transport and other functions of the light-emitting electron transport layer 2 are facilitated. At the same time, in the process of preparing the electron transport layer 2 by spin coating or the like, the presence of glycerol will increase the viscosity of the liquid used to form the electron transport layer 2, reduce its volatilization rate, and make the electron transport layer 2 have a more suitable film formation rate, thereby improving the film formation quality of the electron transport layer 2. Therefore, by introducing glycerol into the electron transport layer 2, the charge transfer between the electron transport layer 2 and the perovskite light absorption layer 3 can be promoted, the fluorescence quenching effect can be enhanced, and the photoelectric performance and efficiency of the perovskite solar cell can be improved.
[0027] Continue to refer Figure 1 The electron transport layer 2 may include a dense electron transport layer 21 (dense thin film layer), and a mesoporous electron transport layer (mesoporous thin film layer) 22 located between the dense electron transport layer 21 and the perovskite light absorbing layer 3. Glycerol exists in the dense electron transport layer 21, which is conducive to further optimizing the performance of the electron transport layer 2 and improving the photoelectric performance and efficiency of the perovskite solar cell.
[0028] Specifically, in the embodiment of the present invention, on the one hand, glycerol is introduced into the dense electron transport layer 21 to facilitate the performance of its charge transport function; on the other hand, as mentioned above, in the process of preparing the dense electron transport layer 21 by dynamic spin coating and the like, the film formation rate is greatly affected by the ambient temperature. For example, in an air atmosphere, a higher room temperature will increase the film formation rate, thereby affecting the film quality of the dense electron transport layer 21. In the embodiment of the present invention, the presence of glycerol can increase the viscosity of the slurry used to form the dense electron transport layer 21, thereby reducing its volatilization rate, so that the dense electron transport layer 21 has a more suitable film formation rate, thereby optimizing the film formation quality of the dense electron transport layer 21, and thereby improving the photoelectric performance and efficiency of perovskite solar cells.
[0029] Generally, the electron transport layer 2 includes an electron transport material, which may include a metal oxide (such as TiO 2 SnO 2 etc.) and / or PCBM etc.
[0030] In the embodiment of the present invention, the electron transport material in the electron transport layer 2 may include TiO 2 The electron transport layer 2 can be specifically a titanium dioxide layer, and the dense electron transport layer 21 and the mesoporous electron transport layer 22 can both be titanium dioxide layers, that is, the dense electron transport layer 21 can be a titanium dioxide dense layer (c-TiO 2 ), the mesoporous electron transport layer 22 may be a titanium dioxide mesoporous layer (m-TiO 2 ).
[0031] As mentioned above, TiO 2 There are problems such as a large bandgap and low electron mobility, and in the process of preparing the electron transport layer 2 (i.e., the titanium dioxide layer) by spin coating or the like, the film formation rate is greatly affected by factors such as the ambient temperature. For example, under higher room temperature conditions, the film formation rate will increase, thereby affecting the film formation quality and performance of the titanium dioxide layer. In the embodiments of the present application, by introducing glycerol into the titanium dioxide layer, these problems can be effectively overcome, and the titanium dioxide layer can function as the electron transport layer 2, thereby improving the photoelectric performance and efficiency of the perovskite solar cell.
[0032] In the present invention, the mesoporous electron transport layer 22 can have the mesoporous morphology and structure of a conventional mesoporous electron transport layer 22 in the art, and the dense electron transport layer 21 can have the dense morphology and structure of a conventional dense electron transport layer 21 in the art, without any particular limitation.
[0033] In addition, the transparent conductive layer 1 is formed of a transparent conductive material, which may specifically include transparent conductive glass. In some preferred embodiments, the transparent conductive layer 1 may include FTO (fluorine-doped tin oxide) conductive glass.
[0034] In addition, the above-mentioned perovskite absorption layer may include metal halide and / or organic halide, the metal halide may include metal iodide, for example, lead iodide; the organic halide may include organic iodide and / or organic chloride, for example, iodomethane and / or chloromethylamine, etc., but is not limited thereto.
[0035] In addition, the hole transport layer 4 includes a hole transport material. For example, the hole transport layer 4 is a Spiro-OMeTAD hole transport layer 4 formed of Spiro-OMeTAD.
[0036] In general, if Figure 1As shown, the perovskite solar cell further comprises a counter electrode 5, which may comprise a metal, for example, a metal electrode formed of a metal, and the metal comprises, for example, gold (Au).
[0037] Continue to refer Figure 1 The side of the transparent conductive layer 1 facing the perovskite light absorbing layer 3 includes a first region 11 and a second region 12 (or conductive region), the electron transport layer 2, the perovskite light absorbing layer 3 and the hole transport layer 4 are sequentially stacked in the first region 11 of the transparent conductive layer 1, that is, the first region 11 is covered by these layers, and the second region 12 is not covered by these layers, wherein a counter electrode 5 is respectively provided on a side of the hole transport layer 4 facing away from the perovskite light absorbing layer 3 and on the second region 12. Specifically, as Figure 1 As shown, the counter electrode 5 has multiple (such as Figure 1 As shown, the number of counter electrodes 5 is 7), wherein one counter electrode 5 is arranged in the second region 12 of the transparent conductive layer 1, and the remaining counter electrodes 5 are arranged on the side of the hole transport layer 4 away from the perovskite light absorption layer 3. These counter electrodes 5 can be specifically evenly distributed on the side of the hole transport layer 4 away from the perovskite light absorption layer 3, for example, distributed in an array on the side of the hole transport layer 4 away from the perovskite light absorption layer 3.
[0038] The present invention also provides a method for preparing the above-mentioned perovskite solar cell, which comprises the following steps:
[0039] S1. Pre-treating the transparent conductive layer 1. The pre-treating process includes: cleaning the transparent conductive layer 1 with a cleaning agent, drying it, and then performing ultraviolet ozone treatment; wherein the cleaning agent includes one or more of water, acetone, isopropyl alcohol, ethanol, and glass cleaning agent.
[0040] The glass cleaning agent may be a conventional glass cleaning agent in the art, which includes, for example, a surfactant and water, and may be commercially available or homemade according to conventional methods in the art.
[0041] In specific implementation, a variety of cleaning agents can be used to ultrasonically clean the transparent conductive layer 1 (such as FTO conductive glass) in sequence, for example, water, glass cleaning agent, isopropanol, ethanol and water are used to ultrasonically clean the transparent conductive layer 1 in sequence (the mass ratio of glass cleaning agent to water is, for example, about 1:3), or acetone, isopropanol, ethanol and water are used to ultrasonically clean the transparent conductive layer 1 in sequence, and the cleaning time each time can be 20 to 40 minutes, for example, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or a range composed of any two thereof, and then placed in a drying equipment such as an oven for drying (drying), and the drying temperature can be 110 to 130°C, for example, 110°C, 115°C, 120°C, 125°C, 130°C or a range composed of any two thereof, so as to remove impurities and moisture on the surface of the transparent conductive layer 1, and then perform ultraviolet ozone treatment.
[0042] The water used may specifically include deionized water.
[0043] The time of the ultraviolet ozone treatment can be 20 to 40 minutes, for example, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or a range consisting of any two of them.
[0044] In the above process, the organic matter on the surface of the transparent conductive layer 1 can be oxidized and degraded by the ultraviolet ozone treatment, and the work function on the surface of the transparent conductive layer 1 can be enhanced, which is beneficial to electron transmission. In the ultraviolet ozone treatment process, the surface of the transparent conductive layer 1 is irradiated with ultraviolet light. The embodiment of the present invention can use a conventional device in the field such as an ultraviolet-ozone generator for ultraviolet ozone treatment, and there is no particular limitation on this.
[0045] S2 , coating a first mixed solution containing an organic titanium source, a first solvent and glycerol on the transparent conductive layer 1 to form a dense electron transport layer 21 .
[0046] Specifically, the first mixed liquid can be spin-coated on the transparent conductive layer 1 by a dynamic spin coating method. Specifically, the first mixed liquid can be spin-coated on the transparent conductive layer 1 at a rotation speed of 1500 to 2500 rpm (the rotation speed can be 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm, 2100 rpm, 2200 rpm, 23000 rpm, 2400 rpm, 2500 rpm or a range composed of any two of them), and then after a first drying treatment, a dense electron transport layer 21 is formed.
[0047] Among them, the first drying treatment can specifically include annealing treatment, the temperature of which can be 110-130°C, for example, 110°C, 115°C, 120°C, 125°C, 130°C or a range consisting of any two thereof, and the time can be 8-12min, for example, 8min, 9min, 10min, 11min, 12min or a range consisting of any two thereof.
[0048] In some embodiments, the first mixed solution is spin-coated on the transparent conductive layer 1 by a dynamic spin coating method, and then annealed at 110-130° C. for 8-12 min to form a dense electron transport layer 21 .
[0049] In a specific implementation, the first solvent, the organic titanium source and glycerol can be mixed, and after being fully shaken to dissolve, a first mixed liquid can be obtained (for example, the first solvent and the organic titanium source are placed in a glass bottle and fully mixed, and then glycerol is added to the obtained mixed solution, and after being fully shaken to dissolve, the first mixed liquid can be obtained); the first mixed liquid is then coated on the transparent conductive layer 1. After the coating is completed, the film layer material on the second area 12 of the transparent conductive layer 1 is removed. Specifically, a cotton swab dipped in isopropyl alcohol can be used to scrape off the film layer material on the second area 12 to expose the second area 12 of the transparent conductive layer 1; the transparent conductive layer 1 coated with the first mixed liquid is then placed on a flat heating table or other equipment for heating to perform a first drying treatment to form a dense electron transport layer 21.
[0050] Specifically, the amount of glycerol used can meet the following requirements: the organic titanium source is calculated as titanium dioxide, and the molar ratio of glycerol to the organic titanium source is 1:200-1:350 (that is, the molar ratio of glycerol to the titanium element in the organic titanium source is 1:200-1:350), for example, 1:200, 1:220, 1:240, 1:250, 1:270, 1:290, 1:300, 1:330, 1:350 or a range consisting of any two of them. By adding low-concentration glycerol, the viscosity of the first mixed solution can be increased, the film formation rate in the preparation process of the dense electron transport layer 21 can be reduced, the film formation quality of the electron transport layer 2 can be optimized, and the electron transport function of the electron transport layer 2 can be exerted, thereby further improving the photoelectric performance and efficiency of the perovskite solar cell.
[0051] In the above process, after annealing, the organic titanium source is converted into TiO 2 , that is, the formed dense electron transport layer 21 is a dense titanium dioxide layer, and glycerol is retained in the formed dense electron transport layer 21.
[0052] Specifically, the organic titanium source may include diisopropoxytitanium bisacetylacetonate.
[0053] In addition, the first solvent may include n-butanol, and specifically anhydrous n-butanol may be used.
[0054] According to the inventors' research, in the above preparation process, diisopropoxy diacetylacetonate titanium, n-butanol and glycerol are used, and a dense electron transport layer 21 is formed by a dynamic spin coating method to improve the photoelectric performance and efficiency of the perovskite solar cell.
[0055] S3 , coating a second mixed solution containing an inorganic titanium source and a second solvent on the dense electron transport layer 21 to form a mesoporous electron transport layer 22 .
[0056] Specifically, the second mixed liquid can be spin-coated on the dense electron transport layer 21 by a static spin coating method. Specifically, the second mixed liquid can be spin-coated on the dense electron transport layer 21 at a rotation speed of 5500 to 6500 rpm (the rotation speed is, for example, 5500 rpm, 5700 rpm, 5900 rpm, 6000 rpm, 6200 rpm, 6400 rpm, 6500 rpm or a range composed of any two of them), and then after a second drying treatment, the mesoporous electron transport layer 22 is formed.
[0057] Among them, the second drying treatment can specifically include annealing treatment, the temperature of which can be 450-550°C, for example, 450°C, 470°C, 490°C, 500°C, 520°C, 540°C, 550°C or a range consisting of any two thereof, and the time can be 40-70min, for example, 40min, 45min, 50min, 55min, 60min, 65min, 70min or a range consisting of any two thereof.
[0058] In some embodiments, the second mixed solution is spin-coated on the dense electron transport layer 21 by static spin coating, and then annealed at 450-550° C. for 40-70 min to form the mesoporous electron transport layer 22 .
[0059] In a specific implementation, the inorganic titanium source and the second solvent can be placed in a glass bottle and stirred thoroughly. For example, a magnet is added thereto for magnetic stirring. The stirring time can be specifically 20 to 30 hours. The obtained mixed solution is the second mixed solution. The second mixed solution is then coated on the side of the dense electron transport layer 21 facing away from the transparent conductive layer 1. After the coating is completed, the film layer material on the second area 12 of the transparent conductive layer 1 is removed. Specifically, a cotton swab soaked in isopropyl alcohol can be used to scrape off the film layer material on the second area 12 to expose the second area 12 of the transparent conductive layer 1. Subsequently, the entire substrate (including the transparent conductive layer 1, the dense electron transport layer 21 formed on the transparent conductive layer 1, and the second mixed solution coated on the dense electron transport layer 21) is placed on a flat heating table and other equipment for heating to perform a second drying treatment to form a mesoporous electron transport layer 22.
[0060] Specifically, the inorganic titanium source may include TiO 2.
[0061] Additionally, the second solvent may include ethanol.
[0062] In addition, the mass ratio of the inorganic titanium source to the second solvent may be 1:(7-9), for example, 1:7, 1:7.5, 1:8, 1:8.5, 1:9 or a range consisting of any two thereof.
[0063] S4, forming a perovskite light absorption layer 3 on the mesoporous electron transport layer 22.
[0064] Specifically, the perovskite light absorbing layer 3 is formed on the side of the mesoporous electron transport layer 22 away from the dense electron transport layer 21. In the specific implementation, the material used to form the perovskite light absorbing layer 3 (such as the aforementioned metal halide and / or organic halide, etc.) can be mixed with the third solvent, and after sufficient stirring (the stirring time can be specifically 4 to 5 hours), a perovskite precursor solution is obtained; the perovskite precursor solution is spin-coated on the mesoporous electron transport layer 22, specifically, the spin coating can be performed at a rotation speed of 3500 to 4500 rpm (the rotation speed is, for example, 3500 rpm, 3700 rpm, 3900 rpm, 4000 rpm, 4200 rpm, 4400 rpm, 4500 rpm or a range composed of any two thereof), and an anti-solvent is dripped on the wet film formed on the mesoporous electron transport layer 22 (specifically, the anti-solvent can be dripped about 20 seconds before the end of spin coating). After the spin coating is completed, annealing is performed to form the perovskite light absorbing layer 3.
[0065] The annealing process may include step annealing, i.e., at least two annealing processes are performed, the annealing temperature increases successively, the annealing time may also increase successively, or the time of each annealing process is substantially the same. By performing at least two annealing processes, annealing may be performed at a lower temperature first, so that the solvent evaporates more slowly to grow larger perovskite grains, thereby facilitating the optimization of the photoelectric effect of the perovskite solar cell, and then annealing may be performed at a higher temperature to fully remove the solvent.
[0066] In some specific embodiments, the annealing process includes sequentially performing a first annealing treatment and a second annealing treatment. The temperature of the first annealing treatment can be 110-120°C and the time can be 3-5 minutes. The temperature of the second annealing treatment can be 140-160°C and the time can be 5-10 minutes. That is, the sample after spin coating is annealed at 110-120°C for 3-5 minutes, and then annealed at 140-160°C for 5-10 minutes to form the perovskite light absorbing layer 3.
[0067] The third solvent may include dimethyl sulfoxide (DMSO) and / or dimethylformamide (DMF), preferably a mixed solvent of DMSO and DMF, and the anti-solvent may include diethyl ether.
[0068] S5 , forming a hole transport layer 4 on the perovskite light absorption layer 3 .
[0069] Specifically, the hole transport layer 4 is formed on the side of the perovskite light absorbing layer 3 facing away from the mesoporous electron transport layer 22, which can be formed by conventional methods in the art such as spin coating, for example, by spin coating Spiro-OMeTAD on the perovskite light absorbing layer 3, and after oxidation for 10 to 14 hours, a Spiro-OMeTAD hole transport layer 4 is formed.
[0070] After the spin coating is completed, the film material on the second area 12 of the transparent conductive layer 1 is removed. Specifically, a cotton swab soaked with γ-hydroxybutyrolactone (GBL) can be used to scrape off the film material on the second area 12 to expose the second area 12 of the transparent conductive layer 1.
[0071] S6: forming a counter electrode 5 on the second region 12 of the transparent conductive layer 1 and the hole transport layer 4 to produce a perovskite solar cell.
[0072] Specifically, the counter electrode 5 can be formed by vacuum evaporation, for example, Au electrode can be formed by vacuum evaporation. In specific implementation, vacuum evaporation can be performed by conventional evaporation devices in the art such as vacuum coating apparatus to form the counter electrode 5, thereby manufacturing a battery device (i.e., a perovskite solar cell).
[0073] The present invention is further described below through specific examples and comparative examples.
[0074] Example 1
[0075] S1. Pretreatment of FTO conductive glass
[0076] The FTO conductive glass was ultrasonically cleaned with acetone, isopropanol, ethanol, and deionized water in sequence, with each cleaning time being 30 minutes.
[0077] Then the FTO conductive glass was placed in an oven and dried at 120°C;
[0078] The dried FTO conductive glass was treated with UV-ozone for 30 min;
[0079] S2. Formation of a dense electron transport layer
[0080] Take 150 μL of diisopropoxy diacetylacetonate titanium (diisopropoxy diacetylacetonate titanium from Alfa, 75% isopropanol solution), add 2.4 mL of anhydrous n-butanol, and add glycerol (the amount of glycerol added satisfies the glycerol and TiO2 ratio shown in Table 1). 2 The mixture was shaken to obtain a first mixed solution;
[0081] The first mixed solution was spin-coated on the FTO conductive glass at a rotation speed of 2000 rpm by a dynamic spin coating method, and then annealed at 120° C. for 10 min to form a dense electron transport layer;
[0082] S3. Formation of Mesoporous Electron Transport Layer
[0083] Titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:8 and stirred for 12 hours to obtain a second mixed solution;
[0084] The second mixed solution was spin-coated on the dense electron transport layer at a rotation speed of 6000 rpm by a static spin coating method, and then annealed at 500° C. for 50 min to form a mesoporous electron transport layer;
[0085] S4. Formation of perovskite light-absorbing layer
[0086] Iodoformamidine, lead iodide, and chloromethylamine were placed in a mixed solvent of dimethyl sulfoxide and dimethylformamide and stirred for 6 hours to obtain a perovskite precursor solution;
[0087] The perovskite precursor solution was spin-coated on the mesoporous electron transport layer at a rotation speed of 4000 rpm, and ether (anti-solvent) was added dropwise 20 seconds before the spin coating was stopped. After the spin coating was completed, the solution was annealed at 120°C for 5 minutes (the first annealing treatment) and then annealed at 150°C for 5 minutes (the second annealing treatment) to form a perovskite light absorption layer;
[0088] S5. Formation of hole transport layer
[0089] Spiro-OMeTAD was spin-coated on the perovskite light-absorbing layer and oxidized for 12 h to form a hole transport layer;
[0090] S6. Formation of Counter Electrode
[0091] A vacuum coating apparatus was used for vacuum evaporation to form an Au electrode (i.e., a counter electrode) on the side of the hole transport layer facing away from the perovskite light absorbing layer and the second region of the FTO conductive glass (i.e., the exposed conductive region), thereby obtaining a perovskite solar cell (whose cross-sectional structure is shown in FIG. Figure 1 shown).
[0092] Comparative Example 1: The difference from Example 1 is that in step S2, glycerol is not added, and the other conditions are the same as those in Example 1.
[0093] Embodiment 2 to Embodiment 5: The difference from Embodiment 1 is that in step S2, the amount of glycerol used is different, as shown in Table 1. Except for the difference shown in Table 1, the other conditions are the same as those of Embodiment 1.
[0094] Example 6: The difference from Example 1 is that glycerol is not added in step S2, but glycerol is added in step S3 (ie, titanium dioxide and anhydrous ethanol are mixed in a mass ratio of 1:8, and glycerol is added thereto to obtain a second mixed solution).
[0095] The open circuit voltage (Voc), current density (Jsc), fill factor (FF) and power conversion efficiency (PCE) of the perovskite solar cells of each embodiment and comparative example were measured as follows: Figure 1 shown.
[0096] Table 1
[0097]
[0098] * The amount of glycerol in Table 1 is the amount of glycerol and TiO 2 The molar ratio of TiO 2 (based on the molar ratio of glycerol to the titanium source used).
[0099] It can be seen that, relative to Comparative Example 1, the introduction of glycerol into the electron transport layer of Examples 1 to 6 enables the perovskite solar cells to have higher open circuit voltage, fill factor and energy conversion efficiency (photoelectric conversion efficiency), thereby improving the photoelectric performance and efficiency of the perovskite solar cells.
[0100] Among them, compared with Example 2 and Example 5, the amount of glycerol used in Example 1, Example 3 and Example 4 is within a more suitable range, showing more excellent photoelectric performance and efficiency.
[0101] Among them, compared with Example 6, Example 1 introduces glycerol into the dense electron transport layer, showing more excellent photoelectric performance and efficiency.
[0102] The steady-state photoluminescence spectra of the perovskite solar cells of Example 1 and Comparative Example 1 are shown in Figure 2 , transient photoluminescence spectrum is shown in Figure 3 , the relationship curve between current density and voltage (JV curve) is shown in Figure 4 , which further illustrates that the introduction of glycerol into the electron transport layer can effectively improve the photoelectric performance and efficiency of perovskite solar cells.
[0103] In the description of the present invention, terms such as "first" and "second" are used only for descriptive purposes, such as distinguishing between components to more clearly illustrate / explain the technical solution, and cannot be understood as indicating or implying the number of the indicated technical features or the order with substantial significance.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A perovskite solar cell, characterized in that: The invention comprises a transparent conductive layer, an electron transport layer, a perovskite light absorbing layer and a hole transport layer which are stacked in sequence, and the electron transport layer comprises glycerol.
2. The perovskite solar cell according to claim 1, characterized in that The electron transport layer includes a dense electron transport layer and a mesoporous electron transport layer located between the dense electron transport layer and the perovskite light absorbing layer, and the glycerol exists in the dense electron transport layer.
3. The perovskite solar cell according to claim 1 or 2, characterized in that: The electron transport layer is a titanium dioxide layer.
4. The perovskite solar cell according to claim 1 or 2, characterized in that: The transparent conductive layer includes FTO conductive glass.
5. A method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The following steps are involved: Applying a first mixed solution containing an organic titanium source, a first solvent and glycerol on the transparent conductive layer to form a dense electron transport layer; Applying a second mixed solution containing an inorganic titanium source and a second solvent on the dense electron transport layer to form a mesoporous electron transport layer; A perovskite light absorption layer and a hole transport layer are sequentially formed on the mesoporous electron transport layer to obtain the perovskite solar cell.
6. The method for preparing a perovskite solar cell according to claim 5, characterized in that: Before applying the first mixed liquid on the transparent conductive layer, the transparent conductive layer is pretreated, and the pretreatment process includes: cleaning the transparent conductive layer with a cleaning agent, drying it, and then performing ultraviolet ozone treatment; wherein the cleaning agent includes one or more of water, acetone, isopropyl alcohol, ethanol, and glass cleaning agent.
7. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The organic titanium source is calculated based on titanium dioxide, and the molar ratio of the glycerol to the organic titanium source is 1:200 to 1:
350.
8. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The organic titanium source includes diisopropoxy diacetylacetonate titanium; And / or, the first solvent comprises n-butanol.
9. The method for preparing a perovskite solar cell according to claim 5 or 8, characterized in that: The first mixed solution is spin-coated on the transparent conductive layer by a dynamic spin coating method, and then annealed at 110-130° C. for 8-12 minutes to form the dense electron transport layer.
10. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The inorganic titanium source includes titanium dioxide; and / or, the second solvent comprises ethanol; and / or, the mass ratio of the inorganic titanium source to the second solvent is 1:(7-9); And / or, the second mixed solution is spin-coated on the dense electron transport layer by static spin coating, and then annealed at 450-550° C. for 40-70 min to form the mesoporous electron transport layer.
Citation Information
Patent Citations
Semiconductor film and semiconductor element
CN104471679A
Perovskite solar cell and preparation method thereof
CN115172591A
Electron transport film layer and application
CN115440894A